2015
DOI: 10.1371/journal.pone.0132768
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Autophagic Function Influences the Progressive Decline of Adult Drosophila Behaviors

Abstract: Multiple neurological disorders are characterized by the abnormal accumulation of protein aggregates and the progressive impairment of complex behaviors. Our Drosophila studies demonstrate that middle-aged wild-type flies (WT, ~4-weeks) exhibit a marked accumulation of neural aggregates that is commensurate with the decline of the autophagy pathway. However, enhancing autophagy via neuronal over-expression of Atg8a (Atg8a-OE) reduces the age-dependent accumulation of aggregates. Here we assess basal locomotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(100 citation statements)
references
References 73 publications
1
98
0
1
Order By: Relevance
“…As flies do not internally regulate their body temperature, even subtle differences in environmental temperature exposure can alter their lifespan. 13,[51][52][53][54] Despite the lack of a closed circulatory system, even tissues such as heart muscle change with age in a similar manner as human cardiac aging. 44 As far back as the 1920s, D. melanogaster was used as a model of aging to demonstrate that lifespan can be heritable and that metabolic rate inversely correlates with lifespan, the basis for the rate-of-living hypothesis.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As flies do not internally regulate their body temperature, even subtle differences in environmental temperature exposure can alter their lifespan. 13,[51][52][53][54] Despite the lack of a closed circulatory system, even tissues such as heart muscle change with age in a similar manner as human cardiac aging. 44 As far back as the 1920s, D. melanogaster was used as a model of aging to demonstrate that lifespan can be heritable and that metabolic rate inversely correlates with lifespan, the basis for the rate-of-living hypothesis.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 99%
“…[47][48][49][50] As in other animals, aging in D. melanogaster has been shown to affect motor behavior, mating activity, and brain morphology. 13,[51][52][53][54] Despite the lack of a closed circulatory system, even tissues such as heart muscle change with age in a similar manner as human cardiac aging. 55 When genes underlying human neurodegeneration due to protein aggregation are expressed in D. melanogaster, age-related protein aggregation occurs by the same mechanism as in human brains.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 99%
“…Studies with Drosophila show that the accumulation of neural aggregates observed with aging is associated with a reduction in the autophagy pathway. These neural aggregates lead to behavior impairments that can be resolved with the maintenance of autophagy pathways in neurons (62). In animal models of Alzheimer's disease, a basal circadian rhythm that controls macroautophagy may be necessary to limit cognitive decline and amyloid deposition (63).…”
Section: Circadian Rhythm and The Modulation Of Autophagymentioning
confidence: 99%
“…Studies with Drosophila demonstrate that neural aggregate accumulation observed with aging is linked to a reduction in the autophagy pathway. These neural aggregates lead to behavior impairments that can be resolved with the maintenance of autophagy pathways in neurons (99). In addition, autophagy is involved in a number of degenerative disorders such as cognitive decline (14, 56, 100), AD (40, 48, 83, 101, 102), Parkinson’s disease (11, 87, 98, 103), Huntington’s disease (59, 104, 105), DM (14, 17, 40, 89, 106, 107), and aging processes (8, 40, 85, 91, 108111).…”
Section: Autophagy and Apoptosismentioning
confidence: 99%